PENYULUHAN DAN PELATIHAN PENINGKATAN KUALITAS AIR SUNGAI CITARUM MELALUI PEMANFAATAN ECENG GONDOK DAN PENATAAN LINGKUNGAN DAS CITARUM - Asih Wijayanti; Bambang Iswanto; Ina Krisantia; Riana Ayu Kusumadewi (Universitas Trisakti, 2022)
In Sukaluyu Village as well as along the Citarum Karawang watershed area there are lots of water hyacinth plants, can absorb pollutants contained in wastewater while reducing the amount of water hyacinth in the waters, is a solution that can be applied in the village. Utilization of water hyacinth as an adsorbent is also one of the appropriate technologies in environmental conservation. Likewise, the arrangement of the Citarum watershed environment will make the living environment more beautiful and comfortable. For this reason, it is important to conduct counseling and training to the community to be able to use water hyacinth leaves as an adsorbent that can be used as a material for purifying wastewater that pollutes the Citarum River. The methods used were socialization and training on the use of adsorbents from water hyacinth leaves and online landscape plant design. The goal is to invite the people of Sukaluyu Village to actively participate in creating a clean and comfortable environment. The results of the implementation of this PKM activity can be concluded that this PKM activity can add insight to the members of the Environmental Friendly Community and the community in Sukaluyu Village, Teluk Jambe Timur District, Karawang Regency regarding the processing of domestic and industrial liquid waste that contains B3, especially regarding the use of water hyacinth leaves as adsorbent and structuring the Citarum watershed environment to create a comfortable and prosperous living environment.